THE RELATIONSHIP BETWEEN PRACTICE PREPAREDNESS AND DENTISTS’ MENTAL CONDITION IN SEMARANG DURING CORONAVIRUS DISEASE 2019 (COVID-19) PANDEMIC - Ardlina, Nira; Hanindriyo, Lisdrianto; Priyono, Bambang (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: This study aims to discover the practice preparedness and dentists’ mental condition in Semarang during Coronavirus Disease 2019 (COVID-19) pandemic.Method: This is an observational analytic study with a cross-sectional online study design. Subjects in this study is 171 members of persatuan dokter gigi Indonesia (PDGI) Semarang branch. Research subject was asked to fill questionnaire on practice preparedness during COVID-19 pandemic and depression anxiety stress scale (DASS-42) in Indonesian shared by researchers through Google form link. Data was analyzed using Spearman correlation, Mann-Whitney, and multinomial logistic regression tests.Result: Bivariate test result showed significant correlation between practice preparedness and DASS depression score (p =0.021 and r=-0.176) and anxiety DASS score (p=0.018 and r=-0.181). There was a significant correlation between training and DASS score depression (p=0.023), anxiety (p=0.025), and stress (p=0.040). Multinomial logistic regression multivariate test result depicted a significant relationship between training and moderate depression (p=0.04 and OR=5.65). Dentists with no training have a higher risk of 5.65 times on moderate depression compared to those with training during COVID-19 pandemic and infectious disease prevention and control training.Conclusion: The better practice preparedness, the milder depression and anxiety of dentists during pandemic. Practice preparedness does not affect dentists’ stress during COVID-19 pandemic. Training may also have an impact on dentists’ depression during COVID-19 pandemic.